KEBIJAKAN PERUMUSAN SISTEM PEMIDANAAN TERHADAP SANKSI PIDANA KERJA SOSIAL SEBAGAI ALTERNATIF PIDANA PENJARA JANGKA PENDEK DALAM KONTEKS PEMBAHARUAN HUKUM PIDANA DI INDONESIA - Adhitya Pradhana NP, Eko Soponyono*), R.B.Sularto (Diponegoro Law Journal, 2013)
Criminal service order is an alternative short-term imprisonment. that arise due to public discontent against imprisonment and criminal regarded as less effective. Imprisonment also cause negative impacts such as over capacity, dehumanization, educational crime by criminals. Therefore, look for alternative short-term imprisonment, criminal, one of which social work as deemed appropriate by the sentencing not only protect the interests of the community but also protect the interests of individual convicts As for the problems in this paper are: First, how the system of policy formulation punishment for criminal juvenile social work as an alternative to short prison term in the context of criminal law reform in Indonesia. Secondly, What is the policy formulation criminal system against criminal sanctions of social work as an alternative short-term imprisonment in Indonesia in comparative studies.The study used the normative juridical approach is also equipped with juridical comparative historical and juridical approach. Data were analyzed descriptively include historical and comparative analysis. Data collection use with library research and overall the data were analyzed qualitatively.The results showed that: 1) criminal sanctions policy of social work as an alternative to short-term imprisonment in the penal code in force in the territory of the Republic of Indonesia no. Social work criminal policies contained in Law No. 11 of 2012 on the Criminal Justice System Children. Criminalization use social sanctions for child labor use certain terms in accordance with legal regulations. 2) forms an alternative to imprisonment continue to be pursued so that eventually formed the Standard Minimum Rules for Non-Custodial Measures (Tokyo Rules) in which there are criminal social work (community service orders) as a form of witness to the non-custodial. In criminal law reform in Indonesia's criminal social work adopted and then encapsulated in the current Criminal Code Bill 2012. Based on the comparison with foreign countries, namely Malaysia Penal Code and Philippine criminal system towards the formulation of social work criminal sanctions as an alternative to short prison term in Indonesia in the legislation in Indonesia is currently no. Criminal formulation work should be applied throughout the territory of Indonesia, such as the formulation contained in Negara Malaysia and the Philippines. Suggestions can be submitted to the government for formulation of policies of social work in the criminal laws and regulations in Indonesia (The concept of the new Penal Code) should consider the advantages and disadvantages/successful application of criminal social work in other countries, so the criminal can be applied to social work effectively as alternative short-term criminal in Indonesia